Pengaruh Faktor Internal dan Eksternal terhadap Kinerja Keuangan Bank Umum Syariah Periode 2019-2023 - Nazma Laelatus Sai’dah; Yayat Rahmat Hidayat; Irma Yulita Silviany (UNISBA Press, 2024)
Abstract. Islamic banking in Indonesia has experienced rapid development in recent years. The measurement of a company's financial performance often uses financial ratio measurements, including financial performance measurement in Islamic banking. The calculation of financial ratios is carried out to show the quality of the bank's financial performance. Good financial performance is the key to the success of Islamic banks in achieving their goals. This study aims to identify Internal Factors (CAR) and External Factors (Inflation) that can partially and simultaneously influence the financial performance (ROA) of Islamic Commercial Banks (BUS). This study uses a quantitative approach using multiple linear regression analysis with Eviews 12 as the processing tool. The type of research used is secondary monthly data obtained from the official website of the Financial Services Authority (OJK) and the Bank Indonesia (BI), during the period of 2019-2023. The results of the t-hypothesis test prove that CAR and Inflation have a significant partial effect on ROA. Simultaneously, CAR and Inflation have a significant effect on the dependent variable, the value of prob (F-Statistic), which is (0.000000 > α 0.05). The coefficient of determination test (R² Test) for the multiple linear regression model between the independent and dependent variables shows that the independent variables, namely CAR and Inflation, are able to explain the dependent variable ROA by 59.0799%, and 40.9201% is explained or illustrated by variations in other variables not included in this study. Abstrak. Perbankan syariah di Indonesia mengalami perkembangan yang pesat dalam beberapa tahun terakhir. Pengukuran kinerja keuangan perusahaan sering kali menggunakan pengukuran rasio-rasio keuangan, termasuk pengukuran kinerja keuangan pada perbankan syariah. Perhitungan rasio keuangan yang dilakukan guna menunjukkan kualitas kinerja keuangan bank. Kinerja keuangan yang baik menjadi kunci utama keberhasilan bank syariah dalam mencapai tujuannya. Penelitian ini bertujuan untuk mengidentifikasi Faktor Internal (CAR) dan Eksternal (Inflasi) dapat memepengaruhi kinerja keuangan (ROA) Bank Umum Syariah (BUS) secara parsial dan simultan. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan analisis regresi linier berganda dengan Eviews 12 sebagai alat pengolahannya. Jenis penelitian yang digunakan yaitu jenis data sekunder bulanan yang diperoleh d ari situs resmi Otoritas Jasa Keuangan (OJK) dan Bank Indonesia (BI), selama periode 2019 – 2023. Hasil pengujian hipotesis t membuktikan bahwa CAR dan Inflasi secara parsial memiliki pengaruh signifikan terhadap ROA. Secara simultan CAR dan Inflasi memiliki pengaruh signifikan terhadap variabel dependen nilai prob (F-Statistik) yaitu (0.000000 > a 0.05 ). Uji koefisien determinasi (Uji R²) untuk model regresi linier berganda antara variabel independen dan dependen menunjukan bahwa variabel independen yaitu CAR dan Inflasi mampu menjelaskan variabel dependen ROA sebesar 59.0799%, dan 40.9201% dijelaskan atau digambarkan oleh variasi variabel lain yang tidak terdapat dalam penelitian ini.